2015
DOI: 10.1002/eji.201445133
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced immunostimulatory activity of cyclic dinucleotides on mouse cells when complexed with a cell‐penetrating peptide or combined with CpG

Abstract: Recognition of pathogen-derived nucleic acids by immune cells is critical for the activation of protective innate immune responses. Bacterial cyclic dinucleotides (CDNs) are small nucleic acids that are directly recognized by the cytosolic DNA sensor STING (stimulator of IFN genes), initiating a response characterized by proinflammatory cytokine and type I IFN production. Strategies to improve the immune stimulatory activities of CDNs can further their potential for clinical development. Here, we demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…CDNs released from bacterial biofilm can also activate host immune responses . Previous studies showed that CDNs could be used as novel vaccine adjuvants or immunostimulatory molecules for host defense . Intranasal administration with c‐di‐GMP enhances bacteria clearance and protects mice from Klebsiella pneumoniae infection through stimulation of dendritic cell‐meditated responses .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDNs released from bacterial biofilm can also activate host immune responses . Previous studies showed that CDNs could be used as novel vaccine adjuvants or immunostimulatory molecules for host defense . Intranasal administration with c‐di‐GMP enhances bacteria clearance and protects mice from Klebsiella pneumoniae infection through stimulation of dendritic cell‐meditated responses .…”
Section: Introductionmentioning
confidence: 99%
“…(18) Previous studies showed that CDNs could be used as novel vaccine adjuvants or immunostimulatory molecules for host defense. (19)(20)(21)(22) Intranasal administration with c-di-GMP enhances bacteria clearance and protects mice from Klebsiella pneumoniae infection through stimulation of dendritic cell-meditated responses. (23) In addition, c-di-AMP increases autophagy in macrophages and attenuates bacterial virulence through the cytoplasmic surveillance pathway during Mycobacterium tuberculosis infection.…”
Section: Introductionmentioning
confidence: 99%
“…STING is expressed ubiquitously in multiple human tissues and cell lines and has been observed at the plasma membrane, endoplasmic reticulum (ER), and on the surface of the outer mitochondrial membrane [1, 2]. It is well known that STING controlled TLR-independent cytosolic responses to viruses and nucleic acids, being required for the activation of both IRF3 and NF-κB and for induction of the gene expressing IFN-β [6]. Recent evidence suggested that STING gets involved in STING-TBK1-IRF3 signaling pathway by three distinct cytosolic nucleic acid–sensing pathways, RNA sensing through RLRs, DNA detection by DDX41 and the ALR IFI16, and the sensing of bacterial cyclic dinucleotides, such as c-di-GMP (c[G(3’ -5’)pG(3’ -5’)p] or cyclic di-AMP or cyclic GAMP (cGMP–AMP) [2, 79].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a current Phase I clinical study is using the synthetic, STING-activating CDN agonist MIW815 (ADU-S100) to study its safety and efficacy in treating patients with advanced/metastatic solid tumors or lymphomas via intratumoral injections (ClinicalTrials.gov Identifier: NCT02675439). Another study has shown that c-di-GMP can be complexed with simple cell-penetrating peptides that enhance cellular delivery and biological activity in murine splenocytes but also that the bacterial 3′−3′-cGAMP is a superior stimulator of IFN genes ligand than c-di-GMP in human peripheral blood mononuclear cells (Yildiz et al, 2015). A more recent study has shown that expression of an inducible c-di-GMP-producing diguanylate cyclase in Klebsiella pneumonia increased endogenous concentrations of c-di-GMP which attenuated its virulence in the lung of mice (Rosen et al, 2017).…”
Section: Intracellular Recognition Of Dnamentioning
confidence: 99%